On the Analysis of Numerical Methods for Nonstandard Volterra Integral Equation - H. S. Mamba; M. Khumalo (Abstract and Applied Analysis)
We consider the numerical solutions of a class of nonlinear (nonstandard) Volterra integral equation. We prove the existence and uniqueness of the one point collocation solutions and the solution by the repeated trapezoidal rule for the nonlinear Volterra integral equation. We analyze the convergence of the collocation methods and the repeated trapezoidal rule. Numerical experiments are used to illustrate theoretical results.